Extensively Drug-Resistant (XDR) Enteric Fever in Children - Sana Ashraf; Mehtab Hussain; Asma Noreen; Falak Abro; Nadeem Noor; Ramla Rehman (Pakistan Journal of Medicine and Dentistry)
Background: Typhoid and paratyphoid fevers are caused by Salmonella enterica subspecies serovars typhi (Salmonella typhi and Paratyphi) and the term enteric fever is generally used to describe both. This study was done to determine the frequency of extensively drug-resistant (XDR) in children diagnosed with enteric fever at a tertiary care hospital.